IDENTIFICATION OF ABUNDANCE AND MICROPLASTICS REMOVAL EFFICIENCY IN COAGULATION, SEDIMENTATION, AND FILTRATION UNITS IN DAGO PAKAR WATER TREATMENT PLANT WITH CIKAPUNDUNG RIVER AS RAW WATER - Imamah Billah, Nihdati
Microplastics (MPs) has become an environmental focus and has reported that microplastics have been found all over the world, from wastewater, marine waters, freshwater, to drinking water. Research related to microplastics is important, especially in drinking water, because microplastics cannot be digested by humans. This study aimed to determine the abundance of microplastics at the sampling location, determine the characterictics of microplastics found, and determine the microplastics removal efficiency in water treatment plant (WTP). The sampling location was carried out at one of the water treatment plants in Dago area, to be exact at the intake, coagulation inlet, sedimentation outlet, and filtration outlet. Water sampling was done in the rainy and dry seasons. The microplastic abundance of the rainy season at the intake, coagulation inlet, sedimentation outlet, and filtration outlet were 20.61 MPs/L, 16.72 MPs/L, 11.46 MPs/L, and 11.67 MPs/L, respectively. While in the dry season was 6.72 MP/L, 6.22 MP/L, 6.44 MP/L, and 4.39 MP/L, respectively. Based on the measurement results, both in rainy and dry seasons at each sampling locations is generally dominated by the size of 300–1000 ?m, fiber-shaped, and transparent color. Meanwhile, based on the FTIR results the majority of polymer types found are polyester (PES), and some are polyethylene terephthalate (PET). The average removal efficiency of microplastics in WTP in the rainy and dry seasons was 44.77% and 38.05%, respectively. The number of microplastics found is more in the rainy season due to higher wind speed and river flow, causing the MPs to be easily fragmented and increasing the concentration. The removal efficiency at this study is low because the operational and maintenance process has not been optimally operated.